2004
DOI: 10.1111/j.1744-7410.2004.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a candidate nutritive glycoprotein from the albumen gland of the freshwater snail, Helisoma duryi (Mollusca: Pulmonata)

Abstract: Abstract. The albumen gland is a female accessory sex gland that synthesizes and secretes perivitelline fluid around pulmonate eggs. The perivitelline fluid is composed of mainly galactogen and proteins, and is thought to provide nourishment to the embryos during development. We have previously identified the major secretory protein of the albumen gland of the freshwater snail Helisoma duryi as a native glycoprotein of ∼288 kDa, consisting of four 66‐kDa subunits. In this study, the major albumen gland protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
0
8
0
12
Order By: Relevance
“…The presence of variant forms is of interest in suggesting an enhanced spectrum of binding to potential microbial pathogens. A molecule with 83% sequence identity was also identified as the most abundant component of the PVF of the related snail, Helisoma duryi [30]. In larvae of the oyster Crassostrea gigas , LBP/BPI transcripts are upregulated following exposure to bacteria, and LBP/BPI may associate with the epithelium as part of first line of defense during all early stages of larval development [58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of variant forms is of interest in suggesting an enhanced spectrum of binding to potential microbial pathogens. A molecule with 83% sequence identity was also identified as the most abundant component of the PVF of the related snail, Helisoma duryi [30]. In larvae of the oyster Crassostrea gigas , LBP/BPI transcripts are upregulated following exposure to bacteria, and LBP/BPI may associate with the epithelium as part of first line of defense during all early stages of larval development [58].…”
Section: Discussionmentioning
confidence: 99%
“…Although the protein composition has not been systematically studied, Bai et al [2628] found phenoloxidase activity in both the AG and perivitelline fluid of B. glabrata, and associated the activity with SDS-PAGE protein band of 35 kDa. Miller et al [29] recorded pBS11, a transcript in the albumen gland of B. glabrata that has 83% nucleotide identity to HdAGP, a major component of the albumen gland and perivitelline fluid of the closely related snail, Helisoma duryi [30]. HdAGP is assumed to be a nutritive glycoprotein, yet it shares sequence similarity to lipopolysaccharide binding protein/bactericidal permeability-increasing (LBP/BPI) antimicrobial proteins [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente, la información estructural que se conoce sobre proteínas de huevo de moluscos gasterópodos está referida principalmente a su estructura primaria y a las funciones que cumplen. Se han descripto especialmente funciones antibacterianas, antifúngicas y citotóxicas (Iijima et al, 1995, Kisugi et al, 1989, Melo et al, 2000, Mukai et al, 2004, Yamazaki, 1993, Yamazaki et al, 1985. Por el contrario, el conocimiento de la estructura tridimensional de perivitelinas de invertebrados se limita a la OR de P. canaliculata (Dreon et al, 2007.…”
Section: Ensayos Electrofisiológicosunclassified
“…También se ve que las ratas inoculadas muestran inmunorreactividad, evidenciando así que fueron inmunizadas por vía oral. (Benkendorff et al, 2001, Dreon et al, 2004, Iijima et al, 1995, Kamiya et al, 2006, Kisugi et al, 1989, Mukai et al, 2004, Nagle et al, 1999, 2001, Sanchez et al, 2006. En el presente trabajo se pudo demostrar que además pueden tener función neurotóxica.…”
Section: Efecto De La Administración Oral a Ratasunclassified